The Investigation Of Elit Table Tennis Sportsmen In Terms Of Their Risk Evaluations - Mahmut Esat Uzun; Mehibe Akandere; Yalçın Tükel (Türk Spor ve Egzersiz Dergisi, 2020)
Aim of this study is analyzing risk assessment of elite table tennis players. In parallel with this aim, risk assessment level of elite table tennis players is compared in respect to gender, age, education level, marital status, perceived level of income, duration of training and taking part in national team. 186 sportsmen, who play actively table tennis at elite level in different sports club, participated to study. Criterion sampling, which is one of the purposeful sampling method, is used to define participators. Study is supported by descriptive survey model. Research data is gained through Personal Information Forms and Risk Assessment Scale (29). Mann Whitney-U test and Kruskall Wallis-H test, which are non-parametric tests, are used to determine whether there is a statistically significant relationship between independent variables (gender, age, education level, marital status, perceived level of income, duration of training and taking part in national team) and points which are gained through Risk Assessment Scale at analyzing gained data. p value of lt;0.05 was considered statistically significant. The study results show that, points of participators, which are obtained from Risk Assessment Scale and its’ sub-factors, demonstrates meaningful distinction according to gender, education level, duration of training and taking part in national team while it does not show meaningful distinction according to age, marital status and perceived income level. As a conclusion, variables such as gender, education level, duration of training and taking part in national team are effective on risk assessment level at the study which is conducted in order to investigate risk assessment conditions of elite table tennis sportsmen.